Interferon-Inducible LINC02605 Promotes Antiviral Innate Responses by Strengthening IRF3 Nuclear Translocation - Xu, Rui; Yu, Shuang-Shuang; Yao, Ran-Ran; Tang, Rong-Chun; Liang, Jia-Wei; Pang, Xuewen; Zhang, Jun (Frontiers in Immunology, 2021)
Non-coding RNAs represent a class of important regulators in immune response. Previously, by lncRNA chip assays, LINC02605 was identified as a candidate regulator in innate immune response. In this study, we systematically analyzed the functions and mechanisms of action of LINC02605 in antiviral innate immune response. LINC02605 was up-regulated by RNA virus，DNA virus, and type I IFNs in NF-κB and Jak-stat dependent manner. Overexpression of LINC02605 promotes RNA virus-induced type I interferon production and inhibited viral replication. Consistently, knockdown of LINC02605 resulted in reduced antiviral immune response and increased viral replication. Mechanistically, LINC02605 released the inhibition of hsa-miR-107 on the expression of phosphatase and tensin homolog (PTEN). By mimics and inhibitors, hsa-miR-107 was demonstrated to not only inhibit PTEN’s expression but also negatively regulate the antiviral immune response. Knockdown of LINC02605 led to the reduction of PTEN expression both in mRNA and protein levels. Overexpression of LINC02605 had an opposite impact. Moreover, LINC02605 attenuated the serine 97 phosphorylation level of interferon regulatory factor 3 (IRF3) by promoting PTEN expression. Nucleo-plasmic fragmentation assay showed that knocking down LINC02605 inhibited the nuclear localization of IRF3, rendering the host cells more susceptible to viral invasion, while overexpression showed opposite effects. Therefore, LINC02605 is an induced lncRNA by viral infection and plays a positive feedback in antiviral immune response through modulating the nuclear localization of IRF3.